The role of urinary kidney injury molecule-1 in monitoring the child with idiopathic microscopic hematuria - Kızılocak, Hande; Dursun, Hasan; Hasbal, Canan; Hatipoğlu, Sami (Journal of Surgery and Medicine, 2021)
Background/Aim: Idiopathic microscopic hematuria is common during childhood, and numerous factors play a role with varying degrees in its etiopathogenesis. We aimed to investigate whether urinary kidney injury molecule-1 level could be a new indicator to detect a possible renal injury that may cause idiopathic microscopic hematuria. Methods: This prospective case-control study included 38 children between 1-15 years of age who were followed up due to idiopathic microscopic hematuria without hypertension and/or edema and 39 healthy individuals with similar gender distribution. Kidney injury molecule-1, urine culture, microalbumin, calcium, magnesium, uric acid, and creatinine levels in spot urine were measured in both groups. A throat culture and abdominal ultrasound were performed on all those included. Results: No significant differences were found between the patient and control groups in terms of age, gender, weight, and height (P>0.05). Microalbumin, microalbumin to creatinine ratio in spot urine, urinary kidney injury molecule-1 levels, and kidney injury molecule-1 to creatinine ratio were higher among the patients than the controls (P=0.016, P=0.013, P=0.001, and P=0.001, respectively). Conclusion: Urinary microalbumin and kidney injury molecule-1 levels, as well as rates of these two markers to creatinine, may be higher in the children with idiopathic microscopic hematuria. Our findings show that children with microscopic hematuria should be monitored for renal tubular injury and the development of chronic renal disease.